2013
DOI: 10.1163/22134808-00002402
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Swimming — Breaststroke Body Movements Facilitate Vection

Abstract: Visually induced illusory self-motion (vection) was facilitated by active breaststroke arm and body movements. Optic flow was generated by having the standing observer make these arm movements, which were detected by Kinect and incorporated into the display. When generated, this optic flow was either expanding (i.e. congruent with the observer's head motion) or contracting (i.e. incongruent with his/her head motion). Optic flow generated during these active movement conditions was also later played back to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The approach of passively playing back visual displays generated by actively moving observers was described by Kim and Palmisano (2008) , and has since been successfully used by other researchers (e.g., Seno et al, 2013 ). Although it is likely that there would be differences in task demand between conditions requiring active head movement and passive viewing, the potential increase in attentional demand of executing head movements does not appear to significantly alter vection.…”
Section: Methodsmentioning
confidence: 99%
“…The approach of passively playing back visual displays generated by actively moving observers was described by Kim and Palmisano (2008) , and has since been successfully used by other researchers (e.g., Seno et al, 2013 ). Although it is likely that there would be differences in task demand between conditions requiring active head movement and passive viewing, the potential increase in attentional demand of executing head movements does not appear to significantly alter vection.…”
Section: Methodsmentioning
confidence: 99%
“…Observers in such studies typically viewed computer-generated self-motion displays while their bodies were physically in motion. The physical motions that accompanied these optic flow displays have been passive (i.e., externally generated) whole-body motions (Wright et al, 2005), or active (i.e., self-generated) head motions while seated (Kim and Palmisano, 2008, 2010; Ash et al, 2011a,b; Ash and Palmisano, 2012), active breaststroke body movements while standing (Seno et al, 2013a), or active walking on the spot (Palmisano et al, 2014a) or even on a treadmill (Onimaru et al, 2010; Seno et al, 2011a; Ash et al, 2013; Palmisano et al, 2014a). Using the illusory definitions of ‘vection’ outlined above to describe self-motion perception in these situations appears problematic.…”
Section: Challenge 1: Defining Vectionmentioning
confidence: 99%
“…Riecke et al, 2005;Feuereissen, 2008). Some previous studies also reported that body posture can alter vection strength (e.g., Seno et al, 2013;Kano, 1991;Nakamura & Shimojo, 1998;Young & Shelhamer, 1990;Mueller et al, 1994;Allison et al, 2012). For example, some studies reported that vection strength differed with body orientation and body posture (e.g., Kano, 1991;Nakamura & Shimojo, 1998).…”
Section: Introductionmentioning
confidence: 97%